Walking Behaviors by Trip Purposes. Issue 1 (January 2014) - Hatamzadeh, Yaser; Habibian, Meeghat; Khodaii, Ali
Increases in motorized trips and declines in individuals' physical activity have become major challenges for many communities. Many studies have investigated the public health, economic, environmental, transportation, and other benefits of promoting nonmotorized modes of transportation. Studies have suggested a range of policies to be considered by policy makers. A significant portion of the transportation literature is made up of studies that have focused on a single-purpose trip. The present research investigated and compared walking behaviors for a diverse range of trip purposes, including work, study, and shopping trips. A series of behavioral choice models was introduced with a range of explanatory variables, including individual, household, travel, and environmental variables. Of the individual variables, age and gender were found to be significantly related to walking. The results showed that seniors were more likely to walk for work trips. Females were more interested in walking during work and shopping trips; however, females were less active during trips for study purposes. The results showed that individuals who had a car in the household were less motivated to walk for the investigated trip purposes. Time of day was also found to be effective in the decision to walk for various trip purposes. Another significant factor was travel distance, which had diverse effects on walking in all models.